Development of Single‐Fiber Piezocomposite Transducers for 3‐D Ultrasound Computer Tomography. Issue 12 (25th September 2018) - Zapf, Michael; Hohlfeld, Kai; Ruiter, Nicole V.; Pfistner, Patrick; van Dongen, Koen W. A.; Gemmeke, Hartmut; Michaelis, Alexander; Gebhardt, Sylvia E.
Abstract : Ultrasound Computer Tomography (USCT) medical imaging is a promising approach for early detection of breast cancer. At Karlsruhe Institute of Technology (KIT) a 3‐D USCT system is developed. The region‐of‐interest (ROI) of 10 × 10 × 10 cm 3 volume is surrounded by a aperture of 2014 semi‐spherical positioned ultrasound transducers. Results from a first patient study reveals the requirement of a significantly increased ROI to cover bodily variations. Design considerations and simulations show a demand for circular transducers with a diameter of ca. 500 µm, increasing the opening angle of the transducers to ca. 60°. Piezofiber composite technology is predestinated to simply provide circular transducers of the required dimensions. Moreover, piezocomposites based on single PZT (lead zirconate titanate Pb[Zrx Ti1‐x ]O3 ) fibers enable a cost‐effective and series‐production alternative to currently used dice‐and‐fill composites. A transducer design is presented which utilizes individually arranged single piezoceramic fibers with 460 μm in diameter within piezocomposite discs. As a result, fibers are independently addressable as single transducer elements allowing for the desired transducer arrangement. The electrical performance of each piezoceramic fiber is determined proofing a strong dependence both of the coupling coefficient and the resonance frequency from the transducer thickness. In further processing, the piezocomposite discs are connected to printed circuits, integrated into a cylindrical housing, and backfilled with polyurethane. Ultrasound characteristics such as sound pressure and opening angle are evaluated quantitatively. The results show that the transducer opening angles lie in the expected range, that the desired center frequency is achieved and that the bandwidth could be preserved compared to former dice‐and‐fill transducers. Abstract : 3‐D Ultrasound Computer Tomography (3‐D USCT) is an imaging method for early detection of breast cancer, developed at Karlsruhe Institute of Technology (KIT). Piezofiber composite technology can provide circular transducers of the required dimensions and defined arbitrary arrangement and are a cost‐effective alternative. A novel design is shown, electrical and ultrasound acoustic characteristics are evaluated and satisfying results are presented.